2006
DOI: 10.1590/s0103-50532006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physico-chemical and antimicrobial screening studies on 14 and 16-membered hexaazamacrocyclic complexes bearing pendant amine groups

Abstract: Descrevem-se neste trabalho, a síntese e a caracterização de uma série de complexos hexaazamacrocíclicos com anéis de 14 e 16 membros, obtidos pela condensação de 1,2-diaminometano ou 1,3-diaminopropano, formaldeído e hidrato de hidrazina, na presença de sais de metais do primeiro período de transição. ]Cl 2 (where M = Co(II), Ni(II) and Zn(II)), were obtained. Elemental analyses, IR spectra, 1 H NMR, EPR, UV-Vis, magnetic susceptibility and conductivity measurements have ascertained the overall geometry and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…4) of [CuL(ClO 4 ) 2 ] showed a sharp band at 3235 cm -1 assignable to the coordinated secondary amine stretching mode. The presence of this band together with the absence of the m(C=O) of aldehyde in the range 1740-1720 cm -1 supported the occurrence of the condensation reaction [49]. The bands around 2927-2855 cm -1 could be assigned to sp 2 C-H stretching mode of long chain pendant arms.…”
Section: Ft-ir Spectramentioning
confidence: 64%
“…4) of [CuL(ClO 4 ) 2 ] showed a sharp band at 3235 cm -1 assignable to the coordinated secondary amine stretching mode. The presence of this band together with the absence of the m(C=O) of aldehyde in the range 1740-1720 cm -1 supported the occurrence of the condensation reaction [49]. The bands around 2927-2855 cm -1 could be assigned to sp 2 C-H stretching mode of long chain pendant arms.…”
Section: Ft-ir Spectramentioning
confidence: 64%
“…All the complexes exhibit a strong absorption band in 420-450 cm )1 region assignable to m(M-N) vibration [25]. The coordination of nitrato and chloro groups have been ascertained by appearance of bands in the 230-240 cm )1 and 275-300 cm )1 regions, which may reasonably be assigned [32] to m(M-O) of the …”
Section: Infrared Spectramentioning
confidence: 88%
“…Shakir et al have also reported[24,25] many binuclear octaazamacrocyclic complexes by the template condensation reaction.Herein we report the synthesis and characterization of novel binuclear octaazatetraimine macrocyclic complexes, [M 2 LX 4 ] [M = Mn II , Co II , Ni II , Cu II and Zn II ; X = Cl or NO 3 ] resulted from the template condensation reactions of N,N¢-diacetylhydrazine with ophenylenediamine.…”
mentioning
confidence: 98%
“…The paramagnetism of nickel(II) complexes (1) to (5) rules out the possibility of square planar structure and tetrahedral structure can be discarded on the basis of the magnitude of the magnetic moment. Complexes (1) to (5) have magnetic moment values in the region of 2.85-3.45 BM which is typical of an octahedral Ni(II) compound [26,27].…”
Section: Magnetic Momentmentioning
confidence: 99%